2020
DOI: 10.1177/0300060520958968
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to residual gallbladder calculi formation using computed tomography and magnetic resonance imaging combined with clinical data

Abstract: Objective We aimed to investigate risk factors related to remnant gallbladder (RGB) stones. Methods This retrospective study included 73 patients with RGB, in groups with and without RGB calculi. Univariate analyses were used to identify nine variables associated with RGB calculi: sex, age, body mass index (BMI), time to detection, surgical method, length of RGB, angle of RGB and common hepatic duct (CHD), choledocholithiasis, and remnant cholecystitis. Multivariate logistic regression was performed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The rate of remnant cystic duct/gallbladder calculi is reported to be 4.19% following SC [5], and the rate of remnant cholecystitis after SC is 1.4% [6]. In studies that have reported treatment of remnant cholecystitis [6] and symptomatic remnant calculi [8][9][10][11][12], the majority of patients required remnant cholecystectomy. Prior to remnant cholecystectomy, preoperative examination of the biliary anatomy is important to avoid bile duct injury.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of remnant cystic duct/gallbladder calculi is reported to be 4.19% following SC [5], and the rate of remnant cholecystitis after SC is 1.4% [6]. In studies that have reported treatment of remnant cholecystitis [6] and symptomatic remnant calculi [8][9][10][11][12], the majority of patients required remnant cholecystectomy. Prior to remnant cholecystectomy, preoperative examination of the biliary anatomy is important to avoid bile duct injury.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made by other researchers as well. [ 15 , 16 , 20 , 21 ] This suggests that remnant gallbladder or cystic duct stones are frequently encountered even after open cholecystectomy. Mistaken identification of gallbladder and cystic duct junction and subtotal cholecystectomies are the factors responsible for incomplete gallbladder removal.…”
Section: Discussionmentioning
confidence: 99%
“…have postulated that the small incision used in open cholecystectomy may result in inadequate exposure of Calot’s area, leading to incomplete gallbladder excision. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Патологія печінки і жовчовивідної системи / Pathology of Liver and Biliary Excretion System examination, magnetic resonance cholangiopancreatography (MRCP), endoscopic retrograde cholangiopancreatography (ERCP), endoscopic ultrasonography allow in the vast majority of cases before surgery to establish the cause of bile passage violation in patients with CL in the preoperative period, perform decompression of the biliary tract during surgery, and then either eliminate the cause of bile passage violation with minimally invasive interventions, or prepare the patient for the next stage of surgical treatment [4][5][6][7][8][9]. However, it is not always possible to determine the cause of EHC in CL using modern diagnostic methods before and during surgery.…”
mentioning
confidence: 99%